2009
DOI: 10.1254/jphs.08209fp
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Multiple Drug Transporters by Efavirenz

Abstract: Abstract. Efavirenz, an important component of human immunodeficiency virus 1 (HIV-1) therapy, causes substantial drug interactions as an inducer of cytochromes and the transporter ABCB1. So far its effect on the expression of other transporters is unknown. We therefore investigated the effect of long-term exposure of cells to efavirenz on expression of a large number of important drug transporters and on cell proliferation as a surrogate of intracellular availability. LS180 cells were used as a surrogate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 38 publications
5
49
0
Order By: Relevance
“…This conclusion is also consistent with an in vitro study in which sertraline was reported to be a strong inhibitor of P-gp. 25) The involvement of P-gp in the disposition of sertraline and desmethylsertraline is consistent with a recent clinical observation of placental passage of antidepressants. 26) In this study, sertraline and desmethylsertraline exhibited the lowest umbilical cord to maternal serum ratio (0.29) followed by paroxetine (0.54), fluoxetine, (0.64), and citalopram (0.71).…”
Section: Discussionsupporting
confidence: 87%
“…This conclusion is also consistent with an in vitro study in which sertraline was reported to be a strong inhibitor of P-gp. 25) The involvement of P-gp in the disposition of sertraline and desmethylsertraline is consistent with a recent clinical observation of placental passage of antidepressants. 26) In this study, sertraline and desmethylsertraline exhibited the lowest umbilical cord to maternal serum ratio (0.29) followed by paroxetine (0.54), fluoxetine, (0.64), and citalopram (0.71).…”
Section: Discussionsupporting
confidence: 87%
“…The cell line LS180 (available at ATCC, Manassas, VA, USA), a cell line derived from human colon adenocarcinoma, was used to investigate changes of drug transporter mRNA expression by induction [18] and to estimate the reciprocal effects on cytostatic properties of the drugs used.…”
Section: Cell Linesmentioning
confidence: 99%
“…Cells were cultured under standard cell-culture conditions as described previously [18] and were seeded 3 days before the assay.…”
Section: Cell Linesmentioning
confidence: 99%
“…Efavirenz acts as both an inducer and an inhibitor of CYP3A4. In vivo, it induces hepatic but not intestinal CYP3A4 (Mouly et al, 2002), and in vitro studies demonstrated an induction of CYP3A4 transcription by efavirenz (Hariparsad et al, 2004;Weiss et al, 2009). In vitro, efavirenz also acts as a weak CYP3A inhibitor (von Moltke et al, 2001).…”
Section: Introductionmentioning
confidence: 99%